Indigenous storywork : educating the heart, mind, body, and spirit - Archibald, Jo-Ann. (Vancouver : UBC Press, 2008)
"Indigenous oral narratives are an important source for, and component of, Coast Salish knowledge systems. Stories are not only to be recounted and passed down; they are also intended as tools for teaching." "Jo-ann Archibald worked closely with Elders and storytellers, who shared both traditional and personal life-experience stories, in order to develop ways of bringing storytelling into educational contexts. Indigenous Storywork is the result of this research and it demonstrates how stories have the power to educate and heal the heart, mind, body, and spirit. It builds on the seven principles of respect, responsibility, reciprocity, reverence, holism, interrelatedness, and synergy that form a framework for understanding the characteristics of stories, appreciating the process of storytelling, establishing in holistic meaning-making."--BOOK JACKET.
The journey begins -- Coyote searching for the bone needle -- Learning about storywork from Stó:lō elders -- The power of stories to educate the heart -- Storywork in action -- Storywork pedagogy -- A give-away.
Includes bibliographical references (p. [161]-167) and index.
Keywords: Coast Salish Indians -- British Columbia -- Folklore; Storytelling -- Canada; Coast Salish Indians -- Education -- Canada; Older Indians -- British Columbia -- Interviews; Oral tradition -- British Columbia; Coyote (Legendary character); Indiens d'Amérique -- Canada -- Folklore; Indiens d'Amérique -- Colombie-Britannique -- Folklore; Art de conter -- Canada; Indiens d'Amérique -- Éducation -- Canada; Autochtones -- Anciens -- Colombie-Britannique -- Entretiens; Tradition orale -- Colombie-Britannique.; Tricksters; Elders (Native peoples) -- British Columbia -- Interviews; Erziehung; Schule; Mythos; Märchen.; Mündliche Überlieferung.; Erzählen.; Erziehung -- Mythen -- Indianer -- Britisch-Kolumbien.; Mythen -- Erziehung -- Indianer -- Britisch-Kolumbien.; Erzählen -- Schule; Schule -- Erzählen.; Mündliche Tradition -- Salish; British Columbia; Indianer; Küsten-Salish.; Coast Salish Indians; Coyote (Legendary character); Older Indians; Oral tradition; Storytelling; British Columbia; Canada; Folklore; Interviews